Terminological and substantive aspects of collaborative robotics: analysis and recommendations - V.A.; P.P.; A.R.; V.A. (Технічна інженерія, 2022)
The development of industry to the level of Industry 4.0 and the transition to level 5.0 involves fully automated production, where all processes are controlled in real time and taking into account changing external conditions. This is possible due to automation and robotization of production processes. The use of collaborative industrial robots in modern production poses a number of problematic issues not only from the technical side, but also related to the meaningfulness of definitions and correct interpretation, i.e. the unequivocal understanding of their essence, terminology in collaborative robotics when designing robotic technologies at the stage of technological preparation of robotic mechanical assembly production machine and instrument construction: in this case, compliance with ISO production standards is mandatory; in the development of control programs taking into account safety requirements, etc. The above problems do not have a single correct solution, although they are not new in the field of manufacturing and robotics. The work presents a concise analysis of information sources that indicate a variety of approaches and methods of research in this direction, as well as a meaningful interpretation of the most common terms.